Evaluasi Pengembangan Usaha Sapi Bali Di Perkebunan Kelapa Sawit (Studi Kasus di Tiga Kabupaten Mukomuko) - Kurniawan, Cahyardi Ricky; Santoso, Urip; Fenita, Yosi; Badarina, Irma; Nurmeiliasari , Nurmeiliasari (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2024)
Cattle-plant integration is a farming model that implements a mutually beneficial synergy between farming and livestock. The research entitled "Evaluation of Bali Cattle Business Development in oil palm plantations" (Case Study in three sub-district Mukomuko Regency) was carried out exploratory with the aim of evaluating the potential for developing Bali cattle business in oil palm plantations in Mukomuko Regency and formulating a strategy for developing Bali cattle farming business. This study uses a qualitative descriptive method to record, describe and interpret the plans programs of the Mukomuko regency government to support the realization of the integration of oil palm cattle. The data processing and analysis method used is a strategic management concept approach, namely IFE and EFE analysis, SWOT matrix, and IE matrix. The results of the evaluation of the development of the Bali cattle farming business in Mukomuko district show the prospect of developing an integrated Bali cattle farming business with oil palm in terms of geographical aspects, population conditions and the condition of Bali cattle farming. The IFE matrix shows a score of 2.43 and the EFE matrix gets a score of 2.59. Based on the IE matrix, the integration effort of Bali cattle – oil palm is in quadrant V which shows the conditions to be maintained and maintained (hold and maintain). Several alternative strategies were selected based on the priorities that can be offered based on the SWOT matrix analysis tool, IE matrix and linear programming (from the operational side) namely conducting market penetration / product development, improving cattle rearing techniques, developing a program to improve the cattle-oil palm integration business on a business scale more efficient use of cow waste for biogas production and alternative energy sources, recruiting professional human resources in the field of animal husbandry and animal health Maximizing the productivity capacity of Bali cattle and oil palm plantations, implementing five cultivation businesses, maximizing the use of grass around oil palm plantations as a source of animal feed. Keywords: Bali Cattle, Integration,  Kuadran V, Oil Palm, SWOT